The role of digital marketing in enhancing customer satisfaction: an applied study of the Petrochemical plant in the Kingdom of Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aimed to identify the impact of digital marketing with its dimensions (email, website design, social media, mobile applications, online advertisements) on customer satisfaction with its dimensions (service quality, customer expectations, privacy and confidentiality, speed of service delivery) for a Petrochemical Factory in Saudi Arabia. The researcher adopted the descriptive analytical method, developing a questionnaire that was distributed to 440 clients of the Petrochemical Factory in Saudi Arabia.The study found that digital marketing in its various dimensions has a significant impact on customer satisfaction. The study concluded with several recommendations, including focusing on designing an easy-to-use website that provides all the necessary information about the company and customer transaction requirements, which will contribute to the company's progress rather than its decline. It also recommended dedicating staff to continuously monitor feedback on social media networks regarding their services and taking customer opinions as feedback to be used in research and development for improvement.
Keywords: Digital Marketing; Customer Satisfaction; Petrochemical Sector